2002
DOI: 10.1002/1521-396x(200202)189:3<1029::aid-pssa1029>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Small Impurity-Pinned Solitons in Layered Antiferromagnets

Abstract: Layered manganese-halide compounds exhibit quasi-two-dimensional magnetic behavior in the temperature region immediately above the ordering temperature where soliton excitation can be experimentally detected as an Arrhenius, exp(E/T), temperature-dependent electron paramagnetic resonance linewidth, where E is the soliton energy. When a nonmagnetic impurity such as magnesium is introduced into the Mn lattice, experimental linewidth data indicate that the excitation energy is dramatically reduced and the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Recently, Zaspel et al [4,5] have shown that the BelavinPolyakov solitons dominate the thermodynamics in the fluctuation region immediately above the Néel temperature of a large class of nearly classical 2D antiferromagnets. Besides, these authors [6,7] have also shown that the introduction of a very small amount of nonmagnetic impurities into the magnetic sites of a classical 2D antiferromagnet creates a new type of static (impurity-pinned) soliton that affects the Arrhenius, e −Es/T , temperature-dependent EPR linewidth by drastically changing the parameter E s . Using an approach on a discrete lattice, they considered the spin vacancy located at the soliton center and obtained two different impurity-solitons ( the P-soliton and the I-soliton), which were detected in the layered antiferromagnet (C 3 H 7 NH 3 ) 2 M x Mn l−x Cl 4 through EPR measurements [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zaspel et al [4,5] have shown that the BelavinPolyakov solitons dominate the thermodynamics in the fluctuation region immediately above the Néel temperature of a large class of nearly classical 2D antiferromagnets. Besides, these authors [6,7] have also shown that the introduction of a very small amount of nonmagnetic impurities into the magnetic sites of a classical 2D antiferromagnet creates a new type of static (impurity-pinned) soliton that affects the Arrhenius, e −Es/T , temperature-dependent EPR linewidth by drastically changing the parameter E s . Using an approach on a discrete lattice, they considered the spin vacancy located at the soliton center and obtained two different impurity-solitons ( the P-soliton and the I-soliton), which were detected in the layered antiferromagnet (C 3 H 7 NH 3 ) 2 M x Mn l−x Cl 4 through EPR measurements [6,7].…”
mentioning
confidence: 99%
“…If the soliton center coincides with the impurity center, this field theory reproduces the two soliton solutions of Refs. [6,7] and still gives the sizes, energies and configurations of these solitons in an analytical way. For the P-soliton, almost entire space is mapped onto the plane, but part of the spin space sphere around the origin is not included in the mapping.…”
mentioning
confidence: 99%
“…In magnetic materials, impurities may be considered for improving (magnetic impurity) or for vanishing (nonmagnetic, spinless) local magnetic interaction at the positions where they were placed. However, recent reported results have found that the antiferromagnetic correlations around a spin vacancy are not destroyed, rather they appear to be increased [5,6,7]. Such a result has leads to the appearance of a new type of soliton whose energy is lower than its counterpart in the absence of the spinless impurity [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[8], the NLσM supplemented by a static nonmagnetic impurity potential was applied to study such a new soliton. In spite of the investigation be carried out in the low frequency limit, its results were shown to be in excellent agreement with numerical and discrete lattice ones [6,7]. Actually, as presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the idea that topologically nontrivial excitations arise in real physical systems had a strong impact on modern physics. These structures became an object of intensive investigations in many condensed matter models and they are particularly believed to play an important role in magnetic systems [8][9][10][11][12]. Our main interest is to study the configuration and energy of such topological excitations on the surface of a cone.…”
mentioning
confidence: 99%